Does a relationship between type of hip fracture and osteoarthritis exist? : Osteoarthritis and hip fracture - Davut, Serkan; Kalacı, Aydıner (Journal of Surgery and Medicine, 2022)
Background/Aim: Many factors have been associated with the etiology of falls and hip fractures in the elderly. However, only a few studies have examined the relationship between osteoarthritis and hip fractures, which are common in this age group. The aim of this study was to determine the relationship between the knee and hip osteoarthritis (OA) and the type of hip fracture. Methods: Patients who underwent surgery in the Orthopedics and Traumatology Department between January 2017 and December 2021 were eligible to participate in this retrospective cohort study. Patients who were 60 years and older with a hip fracture and adequate medical records and radiographs of bilateral hip and knee joints met the inclusion criteria. Data concerning patient co-morbidities, type of hip fracture, whether they had OA in their hip and knee joints, and the severity of their OA were assessed. The severity of the osteoarthritis presence was categorized with using the Kellgren–Lawrence (KL) classification. To categorize the patients, three groups were identified: (1) femoral neck, (2) trochanteric, and (3) subtrochanteric fracture groups. The presence and severity status of OA in the hip and knee joints and co-morbidity data were compared between the groups. Results: Three-hundred forty-one patients with a M/F ratio of 148/193 are included in this study. Femoral neck fractures occurred in 142 (41.6%), trochanteric fractures in 147 (43.1%), and subtrochanteric fractures in 52 (15.2%) patients. The mean age of the cohort was 76.72 (10.165); The mean age of the patients in the trochanteric group was higher than in the subtrochanteric group (P = 0.001). No effect of any existing co-morbidities on fracture type was observed. The overall prevalence of OA in the cohort that was observed in the hip joint was 34.3% with 33.7% in males and 35.3% in females. These rates were 66.6%, 53.4%, and 76.7% in the knee joint, respectively. No difference could be observed between hip OA presence and any type of hip fracture group (P = 0.833 for right hip, P = 0.865 for left hip). Similar rates of moderate and severe hip OA were found in the femoral neck and trochanteric fracture groups. However, the frequency of moderate hip OA was lower and the frequency of severe hip OA was higher in subtrochanteric fracture group compared to other groups (P = 0.164 for right hip, P = 0.241 for left hip. Knee OA was observed to be more common in the trochanteric fracture group (P = 0.003 for the right knee, P = 0.002 for left knee) and also, the rate of severe OA was higher in the trochanteric fracture group compared to other groups (P = 0.013 for right knee, P = 0.006 for the left knee). Conclusion: In contrast to OA presence in the hip, knee OA presence and severity can be significant risk factors for occurrence of trochanteric type fractures in the elderly.